WEAR RESISTANCE AND FAILURE OF ALLOYS STRENGTHENED BY DISPERSED PHASES UNDER ABRASIVE WEAR - Dvoruk, Volodymyr (Problems of Friction and Wear, 2025)
The article presents the results of the study of the fracture patterns and their effect on the wear resistance of dispersion-hardened alloys: steel 80X20R3T, white cast iron 350X10B8T2, composite KS1 with a reinforcing base of fragmentary relite grains, composite KS2 with a reinforcing base of spherical relite grains. A series of wear resistance of dispersion-hardened alloys corresponding to their location by the value of the rheological parameter was obtained, which indicates the rheological nature of their wear resistance during wear against a monolith and hydroabrasive wear. The controlling role of fracture toughness in the formation of the rheological parameter and wear resistance was established. It is shown that depending on the level of deformation properties, the rheological parameter controls different stages of destruction of dispersion-hardened alloys. Thus, for white cast iron and steel, the stage of crack growth is controlled, at which the level of their plastic deformation is sufficient to slow down the growth of cracks due to the relaxation of stresses at their tips, and for composites - the stage of crack nucleation, when plastic deformation occurs on the scale of monoatomic layers and effectively dissipates the friction work. The rheological and rheological-fatigue parameters are determined as wear resistance criteria that have a direct quantitative relationship with the wear of dispersion-hardened alloys during wear against a monolith and hydroabrasive wear. At the same time, the qualitative nature of wear patterns during wear against a monolith is more adequately reflected by the rheological parameter, and during hydroabrasive wear - by the rheological-fatigue parameter. It has been established that, in addition to increasing the fracture toughness, the reinforcing base of spherical relite grains also promotes the growth of true deformation and localization of its plastic component in a thinner layer of the composite. This entails an increase in the rheological parameter, and, consequently, the wear resistance of the composite with a spherical relite grain shape compared to a fragmentary one.